Numerical simulation of the influence of pores sizes on moisture migration dynamic in masonry wall - M. Nde, N.; Fokwa, D.; Mbessa, M.; T. Tamo, T.; Pettang, C. (International Journal of Engineering and Technology, 2021)
The sometimes extreme hydro-climatic stresses that buildings undergo can lead to significant deterioration which can lead to their collapse. The concern to realize durable works and ensuring a comfortable framework for the life of occupants leads to seek effective solutions, as well for the new construction as for the renovation of old construction, answering the sempiternal problem of harmful action of water on buildings materials. This paper proposes a numerical simulation of moisture migration in concrete building walls, the aim being to highlight the influence of pore size on the kinetics of moisture migration, and its gradient in the wall. A mathematical model taking into account the mechanisms of moisture migration due to liquid moisture gradient and by vapor diffusion is proposed; the discrete formulation of the equa-tion by the numerical scheme of Crank Nicolson is then carried out, and results from computer modeling using Matlab software version 7.10.0.499 (R2010a), show that pore size is a key parameter that influences the dynamics of moisture migration in the wall. Indeed, this parameter qualitatively and quantitatively influences the kinetics of moisture migration, as well as it gradient in the concrete wall. It appears a greater migration dynamic when the pores sizes decrease, means a greater kinetics of moisture migration and lower moisture gradient in the walls at the hygrometric equilibrium, for a decreasing pore size.Â